2011
DOI: 10.1016/j.devcel.2011.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Sonic Hedgehog Shedding Results in Functional Activation of the Solubilized Protein

Abstract: All Hedgehog (Hh) proteins are released from producing cells despite being synthesized as N- and C-terminally lipidated, membrane-tethered molecules. Thus, a cellular mechanism is needed for Hh solubilization. We previously suggested that a disintegrin and metalloprotease (ADAM)-mediated shedding of Sonic hedgehog (ShhNp) from its lipidated N and C termini results in protein solubilization. This finding, however, seemed at odds with the established role of N-terminal palmitoylation for ShhNp signaling activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
117
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(131 citation statements)
references
References 50 publications
13
117
1
Order By: Relevance
“…Despite small differences in the relative abundance of lower and higher molecular weight fractions, all ShhNp mutants multimerized effectively. We thus concluded that all ShhNp mutant forms assemble properly on the cell surface and are exclusively released in multimeric form (29).…”
Section: Shhn and Shhnp Binding To Heparin Ismentioning
confidence: 99%
“…Despite small differences in the relative abundance of lower and higher molecular weight fractions, all ShhNp mutants multimerized effectively. We thus concluded that all ShhNp mutant forms assemble properly on the cell surface and are exclusively released in multimeric form (29).…”
Section: Shhn and Shhnp Binding To Heparin Ismentioning
confidence: 99%
“…2B, asterisk). These results demonstrate that both Hh lipidations contribute to Hh association with the cell membrane (Chamoun et al, 2001;Konitsiotis et al, 2014;Ohlig et al, 2011) to ensure that only fully processed Hh is released (Ohlig et al, 2012). This raises the question of how Hh shedding is controlled.…”
Section: Loss Of Dally Function In Hh-producing Cells Affects Drosophmentioning
confidence: 87%
“…2A). We and others have shown that proteolytic removal of N-and C-terminal lipidated peptides (called shedding) releases bioactive Shh morphogens from the surface of producing cells in vitro (Damhofer et al, 2015;Dierker et al, 2009;Jakobs et al, 2014;Ohlig et al, 2011). We further showed that because of the lack of the N-terminal Hhat acceptor cysteine (C25S or C25A in mouse Shh) (Hardy and Resh, 2012) non-palmitoylated Hh proteins require only C-terminal shedding for their solubilization, whereas most Shh N-termini are left intact (Jakobs et al, 2014).…”
Section: Loss Of Dally Function In Hh-producing Cells Affects Drosophmentioning
confidence: 95%
See 1 more Smart Citation
“…Urinary concentrations of ADAM12 have been shown to correlate with cancer stage, making it a potential biomarker with which to monitor tumor progression (59)(60)(61). ADAM12 facilitates tumor progression by stimulating cell proliferation and survival pathways (62)(63)(64). This is achieved by the proteolytic activation and release (ectodomain shedding) of membrane-bound growth factors, including HB-EGF, erythroblastic leukemia viral oncogene homolg 4, tumor necrosis factor α and tumor growth factor α (40,65).…”
Section: Discussionmentioning
confidence: 99%